Joyful Orphan : Poems - Irwin, Mark, 1953- (Book collections on Project MUSE., 2023)
"Joyful Orphan is a book of witness: species and habitat extinction, war, poverty, technology, history, and race. In this collection, Mark Irwin attempts to find how these worlds interface and affect one another. There are many different ways to become orphaned in the contemporary world, but often it is an attempt to understand the meaning of love continuously translated into languages that one does not know"--